Analisis Pengaruh Return On Equity, Current Ratio, Price Earning Ratio, Debt To Equity Ratio Dan Total Asset Turnover Terhadap Return Saham Pada Perusahaan Yang Termasuk Pada LQ-45 Di Bursa Efek Indonesia Periode 2016-2021 - Muhamad Ory Adrianto; Sugianto Sugianto (Jurnal Akuntan Publik, 2024)
Return is one of the aspects that motivates investors to engage and is also a reward for the investor's courage in bearing the risks of the investment they make. The aim of this research is to determine the effect of Return on Equity, Current Ratio, price earnings ratio, Debt to Equity Ratio and total assets turnover on stock returns in companies included in the LQ-45 index on the Indonesia Stock Exchange in the period 2016-2021. The population in this research are companies on the Indonesian Stock Exchange in the 2016-2021 period. The sampling technique in this research used purposive sampling. Empirical findings prove that NPL ratio factors affect firm value, while other factors namely; Company growth (FG), CAR, Loans (LDR), BOPO, DPK Growth (DG) and profitability partially do not affect the value of the company (Tobin's Q), but affect the value of the company (Tobin's Q) together.